Evidence-based scientific thinking and decision-making in everyday life - Dawson, Caitlin; Julku, Hanna; Pihlajamäki, Milla; Kaakinen, Johanna K.; Schooler, Jonathan W.; Simola, Jaana (SPRINGER, 2025)
In today's knowledge economy, it is critical to make decisions based on high-quality evidence. Science-related decision-making is thought to rely on a complex interplay of reasoning skills, cognitive styles, attitudes, and motivations toward information. By investigating the relationship between individual differences and behaviors related to evidence-based decision-making, our aim was to better understand how adults engage with scientific information in everyday life. First, we used a data-driven exploratory approach to identify four latent factors in a large set of measures related to cognitive skills and epistemic attitudes. The resulting structure suggests that key factors include curiosity and positive attitudes toward science, prosociality, cognitive skills, and openmindedness to new information. Second, we investigated whether these factors predicted behavior in a naturalistic decision-making task. In the task, participants were introduced to a real science-related petition and were asked to read six online articles related to the petition, which varied in scientific quality, while deciding how to vote. We demonstrate that curiosity and positive science attitudes, cognitive flexibility, prosociality and emotional states, were related to engaging with information and discernment of evidence reliability. We further found that that social authority is a powerful cue for source credibility, even above the actual quality and relevance of the sources. Our results highlight that individual motivating factors toward information engagement, like curiosity, and social factors such as social authority are important drivers of how adults judge the credibility of everyday sources of scientific information.